Controllably facile design of electrophoretic-induced film-forming of nano tungsten oxide (VI) and their anti-wetting functionalization. (2nd October 2020) - Guo, Xiaogang; Liang, Taotao; Yuan, Binfang; Wang, Jing; Sun, Qi
Abstract: There is keen interest for designing promising tungsten oxide (VI, WO3 ) films or coatings due to their wide applications in fields of energy, engineering, etc. Thus, this paper firstly introduce a novel convenient method of electrophoretic assembly technique (EAT) in an optimal stable suspension of isopropyl alcohol, PEG-1000 and polyethyleneimine for designing the promising anti-wetting functional WO3 (VI) films with relative rough structures and uniform distribution in mild conditions. The product possess a high crystallinity and pureness by x-ray powder diffraction analysis. The EAT dynamic behaviours of WO3 (VI) nanoparticles are investigated in detail. Moreover, obtained films shows excellent anti-wetting properties after suface modification, and the hydrophobic studies results demonstrate that product have a high static water CA of approximate 169° and keep nearly stable even after ultralong exposure time (360 d), and show outstanding properties of anti-soaking, impacting-proof, and moisture resistance even in high relative humidity (90%). These breakthroughs will substantially push forward the convenient processing of other anti-wetting functional coatings with wide potential applications.